2022
DOI: 10.1093/plcell/koac193
|View full text |Cite
|
Sign up to set email alerts
|

Rapid growth of Moso bamboo (Phyllostachys edulis): Cellular roadmaps, transcriptome dynamics, and environmental factors

Abstract: Moso bamboo (Phyllostachys edulis) shows remarkably rapid growth (114.5 cm/day), but the underlying biological mechanisms remain unclear. After examining more than 12,750 internodes from more than 510 culms from 17 Moso populations, we identified internode 18 as a representative internode for rapid growth. This internode includes a 2-cm cell division zone (DZ), a cell elongation zone up to 12 cm, and a secondary cell wall (SCW) thickening zone. These zones elongated 11.8 cm, produced approximately 570,000,000 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
53
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(84 citation statements)
references
References 72 publications
5
53
2
Order By: Relevance
“…These two zones directly promote internode elongation during the fast growth. Similar growth behavior has also been observed in the internodes of Moso bamboo (Chen et al, 2022). However, to date, the biological mechanisms underlying this sectioned growth remain unknown.…”
Section: Introductionsupporting
confidence: 79%
See 1 more Smart Citation
“…These two zones directly promote internode elongation during the fast growth. Similar growth behavior has also been observed in the internodes of Moso bamboo (Chen et al, 2022). However, to date, the biological mechanisms underlying this sectioned growth remain unknown.…”
Section: Introductionsupporting
confidence: 79%
“…In more than a thousand years of research, bamboo researchers have systematically investigated the growth pattern, anatomical structure, physiological changes, hormonal changes, and proteome and transcriptome profiles during the rapid growth of bamboo shoots (Chen et al, 2022; Cui et al, 2012; Wang et al, 2021; Yang et al, 2021). Recently, through anatomy and transcriptome analysis of a slow‐growing variant, our group demonstrated that the interaction between mechanical force and genes related to cell wall growth plays an important role in regulating cell growth during the rapid growth process of bamboo shoots (Gao et al, 2022; Wei et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Soluble sugar and protein acted synergistically to promote germination and growth of shoots ( Zeng et al., 2019 ). High gibberellin accumulation could reduce the number of bamboo shoots withdrawn ( Chen et al., 2022 ). In addition, it was found that stronger light was beneficial to clone plants to produce more ramets ( Li et al., 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…The content of GAs in dwarf bamboo varieties is also lower than that in normal bamboos, implying that GA plays a major role in the height of Shidu bamboo [ 41 ]. Exogenous application of GA resulted in a significant increase in internode length in bamboo seedlings [ 42 ]. Those results hint that GA may play a dual role in internode elongation between shoots and seedlings of bamboo.…”
Section: Discussionmentioning
confidence: 99%